State-supported language strategies in Azerbaijan: promotion of Azerbaijani and multilingual initiatives - Abdullayev, Ramil Sahib (Litera, 2024)
The wealth of every independent and sovereign country is the abundance of language on its territory, in which the nationalities living there can freely use their languages. In addition to the State language, there are more than 15 languages spoken by ethnic minorities in the Republic of Azerbaijan. In addition to the languages of ethnic minorities, the population of the country uses other foreign languages, which are included in the group of world languages. The objects of research in this article are foreign languages and their relationship to the state language. The legislative acts adopted to regulate the language vector in the country are the subject of research. The author describes in detail and highlights the legislative bodies and government structures that play a crucial role in the development of language policy in the country. In the course of studying language policy, one cannot do without considering the following two main sociolinguistic terms: language regulation and language planning, which are of the nature of state or social impact on the functioning or development of languages in the state. The author mainly used the theoretical method in the study of the article, and also conducted a general analysis of the data. The conclusions are based on legal methods, as well as sociolinguistic methods (statistical and expert assessments). The necessary information in the field of the current language policy in the country was obtained during the analysis of legal documents. Foreign languages of global importance are in great demand among young people, increasingly studying these languages, they delve into the origins of this language, study the history of this country and through this prism the phenomenon of acculturation through language is observed. The author considers in more detail the status of the state language both de jure and de facto, and also considers in detail the position of the most widespread foreign languages in the republic. The language reforms carried out in the Republic of Azerbaijan mainly serve to strengthen the role of the Azerbaijani language as the state language and have the character of linguistic purism. Despite the ongoing reforms in the field of strengthening the state language, we are also considering a balanced language policy with regard to other languages existing on the territory of the Republic of Azerbaijan, the purpose of which is to preserve linguistic pluralism.